ANALISIS EFEKTIVITAS PENGGUNAAN TEKNOLOGI VIRTUAL REALITY DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SD - I Kadek Arta; I Kadek Tediana Saputra; Ni Made Apriatini; Gusti Ayu Putu Intan Kusuma D; Kadek Paria Wati; Ida Bagus Putrayasa; I Nyoman Sudiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of utilizing Virtual Reality (VR) technology in teaching Indonesian language to fifth-grade elementary school students. Employing a quasi-experimental design with a pretest-posttest control group, the research involved two groups: an experimental group using VR-based learning media and a control group employing conventional teaching methods. Data collection instruments included reading comprehension tests, learning motivation questionnaires, and student engagement observations. The results indicated that the use of VR significantly enhanced students' understanding of Indonesian language materials, particularly in reading comprehension and creative writing. Moreover, there was a notable increase in students' motivation and engagement during the learning process. These findings align with previous research demonstrating that VR media can boost student interest and learning outcomes. However, implementing VR technology also presents challenges, such as the need for adequate infrastructure and teacher training. Therefore, integrating VR into Indonesian language instruction at the elementary level holds considerable potential for improving educational quality, provided that sufficient facilities and resources are available..